Genetic prevention of hepatitis C virus‐induced liver fibrosis by allele‐specific downregulation of MERTK. Issue 8 (29th September 2016) - Cavalli, Marco; Pan, Gang; Nord, Helena; Wallén Arzt, Emelie; Wallerman, Ola; Wadelius, Claes
Abstract : Aim: Infection by hepatitis C virus (HCV) can result in the development of liver fibrosis and may eventually progress into cirrhosis and hepatocellular carcinoma. However, the molecular mechanisms for this process are not fully known. Several genome‐wide association studies have been carried out to pinpoint causative variants in HCV‐infected patient cohorts, but these variants are usually not the functional ones. The aim of this study was to identify the regulatory single nucleotide polymorphism associated with the risk of HCV‐induced liver fibrosis and elucidate its molecular mechanism. Methods: We utilized a bioinformatics approach to identify a non‐coding regulatory variant, located in an intron of the MERTK gene, based on differential transcription factor binding between the alleles. We validated the results using expression reporter assays and electrophoresis mobility shift assays. Results: Chromatin immunoprecipitation sequencing indicated that transcription factor(s) bind stronger to the A allele of rs6726639. Electrophoresis mobility shift assays supported these findings and suggested that the transcription factor is interferon regulatory factor 1 (IRF1). Luciferase report assays showed lower enhancer activity from the A allele and that IRF1 may act as a repressor. Conclusions: Treatment of hepatitis C with interferon‐α results in increased IRF1 levels and our data suggest that this leads to an allele‐specific downregulation of MERTK mediated by an allelic effect on the regulatory element containing the functional rs6726639. This variant also shows the hallmarks for being the driver of the genome‐wide association studies for reduced risk of liver fibrosis and non‐alcoholic fatty liver disease at MERTK .